Bioprosthetic Total Artificial Heart Implantation Does Not Induce Chronic Inflammation. Issue 11 (12th October 2022) - Peronino, Christophe; Guerin, Coralie L.; Ivak, Peter; Guyonnet, Léa; Chocron, Richard; Detriché, Grégoire; Latremouille, Christian; Gruest, Maxime; Philippe, Aurélien; Capel, Antoine; Pya, Yuri; Martin, Anne-Céline; et al.
Abstract : The Aeson total artificial heart (A-TAH) has been developed for patients at risk of death from biventricular failure. We aimed to assess the inflammatory status in nine subjects implanted with the A-TAH in kinetics over one year. Laboratory assessment of leukocyte counts, inflammatory cytokines assay, and peripheral blood mononuclear cell collection before and after A-TAH implantation. Leukocyte counts were not significantly modulated according to time after A-TAH implantation (coefficient of the linear mixed effect model with 95% CI, −0.05 (−0.71 to −0.61); p = 0.44). We explored inflammatory cytokine after A-TAH and did not observe, at any time, a modified profile compared to pre-implantation values (all p -values > 0.05). Finally, we compared the distribution of circulating immune cell subpopulations identified based on sequential expression patterns for multiple clusters of differentiation. None of the population explored had significant modulation during the 12-month follow-up (all p -values > 0.05). In conclusion, using a cytokine multiplex assay combined with a flow cytometry approach, we demonstrated the absence of inflammatory signals in peripheral blood over a period of 12 months following A-TAH implantation.